A Review on Foamed Concrete Filled Hollow Section - Pillai, Ganeshwaren; Prof. Madya Ts. Dr. Norashidah Binti Abd Rahman (Recent Trends in Civil Engineering and Built Environment, 2023)
Concrete Filled Hollow Section (CFHS) are becoming on demand composite element in the construction industry due to its high ductility and energy absorption, ease of construction, and elimination of formwork. However, this combination of concrete and steel makes the structural elements heavier and the overall design uneconomical. Therefore, lightweight concrete such as foamed concrete is suggested. Since foamed concrete has a lower strength, steel fibre or polypropylene fibre is added to increase the strength of foamed concrete. The aim of this study is to review the strength of different types of foamed CFHS which are plain foamed CFHS, steel fibre foamed CFHS, and polypropylene foamed CFHS. This is done by analysing the data obtained from the laboratory test conducted from previous study. The test conducted was the axial compression test to evaluate the strength of the foamed CFHS. From the review analysis, steel fibre foamed CFHS is found to have the highest compressive strength and ductility.